Jesus Our Priest : a Christian Approach to the Priesthood of Christ. - O'Collins, Gerald (OUP Oxford, 2010)
In recent years many books have been published in the area of Christology (who is Jesus in himself?) and soteriology (what did he do as Saviour?). A number of notable, ecumenical documents on Christian ministry have also appeared. But in all this literature there is surprisingly little reflection on the priesthood of Christ, from which derives all ministry, whether the priesthood of all the faithful or ministerial priesthood. This present work aims to fill that gap by examining, inthe light of the Scriptures and the Christian tradition, what it means to call Christ our priest. Beginning with a.